WHOLE-BODY VIBRATION EXERCISE IS WELL TOLERATED IN PATIENTS WITH DUCHENNE MUSCULAR DYSTROPHY: A SYSTEMATIC REVIEW - Moreira-Marconi, Eloá; Sá-Caputo, Danubia C; Dionello, Carla F; Guedes-Aguiar, Eliane O; Sousa-Gonçalves, Cintia R; Morel, Danielle S; Paineiras-Domingos, Laisa L; Souza, Patricia L; Kütter, Cristiane R; Costa-Cavalcanti, Rebeca G; Costa, Glenda; Paiva, Patricia C; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Duchenne muscular dystrophy (DMD) is caused by a defective gene located on the X-chromosome, responsible for the production of the dystrophin protein. Complications in the musculoskeletal system have been previously described in DMD patients. Whole body vibration exercise (WBVE) is a treatment that improves musculoskeletal function in movement disorders. The aim of this study was to review the effects of WBVE on functional mobility, bone and muscle in DMD patients. Materials and Methods: Four databases were searched. Three eligible studies were found; all three conclude the management of DMD patients with WBV was clinically well tolerated. The studies used a side-alternating WBV system, frequencies 7 - 24 Hz; and amplitudes 2 - 4 mm. Results: A work indicates that a temporary increase in creatine kinase in DMD during the first days of WBV was observed, but other authors did not find changes. No significant changes in bone mass, muscle strength or bone markers. Some patients reported subjective functional improvement during training. Interpretation: Conclusion: It is concluded that WBV seems to be a feasible and well tolerated exercise modality in DMD patients.